Avaliação das áreas de preservação permanente da região metropolitana de Goiânia a partir da análise legal e de sistema de informação geográfica - Joildes Brasil; Manuel Eduardo Ferreira; Murilo Raphael Dias Cardoso (Confins)
Permanent Preservation Areas (APPs) are spaces specially protected by law, through the Brazilian Forest Code (CFB). These spaces, despite being environmentally fragile, play important ecosystem functions, especially the protection of water resources. However, the irregular use of APPs in rural and urban environments is becoming increasingly common, as in the case of the Metropolitan Region of Goiânia (RMG), Goiás. Given this problem, this article provides an assessment of the situation of PPAs that understand RMG, from the use of remote sensing data and geographic information systems, as strategic tools for decision making processes and management of these spaces. The cartographic products (maps of use and occupation, APPs and conflict of use in APPs) allowed to identify the predominance of cultivated pastures in almost 45% of all mapped APPs (river, springs, lakes and lagoons). In the current scenario, the non-compliance with what is foreseen in the BFC is perceived in all member municipalities of this region, with degradation percentages greater than 40% of APPs. Therefore, attention is drawn mainly to the consequences of this process of de-characterization of protected areas on the quality and quantity of water resources in the research area, which has been experiencing water shortage since 2017, to the point that in 2018 and 2019, the government of Goiás declared a state of water crisis in the RMG. In this sense, it is increasingly urgent a noter position of the Government to regularize these spaces, given the irregular occupation mainly by the use of pastures.